Economic Inclusion and Revenue Improvement Programs as Catalysts for Achieving SDG 8: Insights from INDH Program 3 in Morocco. - ISSAMI, Jihad; CHERQAOUI, Mariam; MORCHID, Meryeme (African Scientific Journal, 2025)
Abstract This study examines the role of economic inclusion and revenue improvement programs in advancing Sustainable Development Goal 8 (SDG 8): Decent Work and Economic Growth, with a particular focus on Morocco’s INDH Program 3 in Kénitra Province. The research explores how targeted initiatives contribute to youth employment, entrepreneurial development, and income improvement in marginalized regions. A mixed-methods approach was employed, combining quantitative data analysis from official reports with qualitative insights gathered through interviews with program beneficiaries and stakeholders. The study’s sample consists of 4,954 program participants aged 18 to 45, including 33% women. The empirical analysis focuses on key variables such as educational background, gender distribution, sectoral focus, and the effectiveness of capacity-building programs. The findings reveal that INDH Program 3 has significantly contributed to job creation and economic inclusion, particularly in the services and crafts sectors, which account for 79% of supported projects. However, challenges persist in achieving gender parity and expanding access to underrepresented fields such as agriculture and education. The study underscores the importance of strengthening gender-focused strategies, diversifying sectoral interventions, and improving post-creation business support to enhance long-term program sustainability. This research contributes to the literature on local economic development by offering an in-depth case study of a government-led inclusion initiative. Policy recommendations emphasize the need for scalable entrepreneurial support mechanisms, tailored financial assistance, and a more inclusive approach to economic participation to maximize impact. Keywords : Economic Inclusion, Sustainable Development Goal 8, INDH Program 3, Youth Employment, Revenue Improvement Programs